JUDICIAL REVIEW UNDANG-UNDANG PERKAWINAN: FLOATING EXECUTION MAHKAMAH KONSTITUSI DAN IMPLIKASINYA TERHADAP KEPASTIAN HUKUM - Fattah, Mohammad; Mustaufiy, Ahmad Syagif Hannany (Al-Amien Prenduan University, Sumenep, 2024)
The Constitutional Court's decisions are not always implemented. This is proven by two Constitutional Court decisions in reviewing the Marriage Law (hereinafter written as UUP) which was